Identifying the challenging characteristics of systems thinking encountered by undergraduate students in chemistry problem-solving of gas laws. Issue 3 (17th May 2019) - Chen, Ya-Chun; Wilson, Kimberley; Lin, Huann-shyang
Abstract : Systems thinking has been an educational priority for more than a decade, yet its related assessment and teaching strategies have been understudied in the chemistry education research community. Through the lens of systems thinking, this study explores how undergraduate students connect and translate their conceptual representations when they are involved in contextualised problem-solving. The 'Contextualised Problem Solving' (CPS) assessment instrument contains four open-ended questions about gas law. Three different cohorts of students registered in a physical science course (2016 Fall, 2017 Spring, 2017 Fall semesters) participated in the problem-solving component of CPS. The results showed that only 8% of students were capable of higher order systems thinking ability when they engaged in problem solving. Over half of the students failed to retrieve essential concepts in problem situations. Most of the participants demonstrated difficulties in organising related systems' components, understanding the cyclic nature of relationships among systems, and identifying limitations in a specific problem context. By identifying the difficulties and challenges of systems thinking experienced by undergraduate students in solving complex chemistry problems, these findings have the potential to provide fresh insights into effective teaching strategies to promote students' higher order thinking skills.